Clinical profile and outcome of COVID-19-positive pregnant mothers admitted in a tertiary care center: A retrospective cohort study from Mizoram, India - Vanremmawii,; Lalrinfela,; Lalduhchhungi,; Vanlalpeka, Harvey; Lalramhluna PC,; Anusuya, Ganesh Shanmugasundaram (Asian Journal of Medical Sciences, 2023)
Background: The clinical profile of COVID-19-positive pregnant mothers and their outcome has not been studied in Mizoram. Aims and Objectives: The objectives was to study the clinical profile of COVID-19-positive pregnant mothers and also to study the positivity rate among the babies born to those pregnant mothers. Materials and Methods: This study was a retrospective cohort of COVID-19-positive pregnant mothers who were admitted in a tertiary care center in Mizoram from July 2020 to September 2021. The data were collected from the case sheets of the patients retrospectively. The babies were also tested for COVID-19 after 24 h after birth by rapid antigen test (RAT). P<0.05 was considered statistically significant. Data analysis was done by coGuide Statistics software, Version 1.0. Results: Out of 81 COVID-19-positive pregnant mothers, majority 56 (69.14%) were in the age group 19–25 years. Only 6 (7.41%) were vaccinated. The most common symptoms observed were fever 35 (43.21%) followed by cough 28 (34.57%). Sixty-five (80.25%) were full term at the time of admission and 36 (44.44%) were primigravida. The mode of delivery was full-term cesarean section 55 (67.90%), term normal vaginal delivery 21 (25.93%), hysterotomy 3 (3.7%), abortion 1 (1.23%), and pre-term vaginal delivery 1 (1.23%). The mortality among pregnant mothers was 3 (3.70%). The positivity rate for babies tested by RAT was 2 (2.47%). Conclusion: The mortality among pregnant mothers was 3.70% and the COVID-19 positivity rate among newborn babies was 2.47%.